210Po/210Pb disequilibria influenced by production and remineralization of particulate organic matter around Prydz Bay, Antarctica. (September 2021) - Chen, Mengya; Chen, Min; Zheng, Minfang; Qiu, Yusheng; Chen, Qianna; Li, Qi
Abstract: Dissolved and particulate 210 Po and 210 Pb were measured to reveal the particle dynamics around Prydz Bay in the austral summer of 2015. The spatial variations of 210 Po activity concentration and 210 Po/ 210 Pb disequilibria are mainly controlled by 210 Po absorption and particle scavenging, and particulate organic matter (POM) remineralization. Different water masses around Prydz Bay show different characteristics of 210 Po/ 210 Pb disequilibria. The activity ratios of total 210 Po to total 210 Pb (expressed as T P o T P b A R ) in Antarctic Surface Water, Winter residual Water, Shelf Water and Thermocline Water are all less than 1.0, indicating that biological absorption and particle adsorption preferentially scavenge 210 Po from these waters. Circumpolar Deep Water shows the highest T P o T P b A R characteristics, and the total 210 Po is in equilibrium or excess to the total 210 Pb, which reflects the effect of POM remineralization. The T P o T P b A R value in the Antarctic Bottom Water is less than 1.0, and it falls between the ratios of Shelf Water and Circumpolar Deep Water, which proves that the formation of Antarctic Bottom Water has an impact on the 210 Po/ 210 Pb disequilibria. f retained is defined to represent the proportion of 210 Po scavenging from the dissolved phase to the particulate phase but suspended in seawater; we found that there is a linear relationship between f retained and particulate organic carbon (POC), silicic acid and phosphate concentrations, indicating that the balance between input (POM remineralization) and removal (biological absorption and particle adsorption) determines the disequilibrium between 210 Po and 210 Pb. Based on the 210 Po/ 210 Pb disequilibria, the POC export from the euphotic zone is estimated to be 4.11–47.82 mmol C m −2 d −1, showing large spatial variability. The POC export on the shelf is generally higher than that on the slope and basin, which corresponds to the spatial variations of phytoplankton biomass and primary productivity. Highlights: Different water masses show different 210 Po/ 210 Pb disequilibria characteristics. Production and remineralization of POM determine the 210 Po/ 210 Pb disequilibria. POC export estimated from 210 Po/ 210 Pb disequilibrium shows a decrease from the shelf to the slope and basin.